2021
DOI: 10.1111/eci.13520
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 re‐infection risk in Austria

Abstract: Background A key question concerning coronavirus disease 2019 (COVID‐19) is how effective and long lasting immunity against this disease is in individuals who were previously infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). We aimed to evaluate the risk of SARS‐CoV‐2 re‐infections in the general population in Austria. Methods This is a retrospective observational study using national SARS‐CoV‐2 infection data from the Austrian epidemiological reporting system. As the primary outcome,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
181
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(195 citation statements)
references
References 29 publications
10
181
2
2
Order By: Relevance
“…Thus, infection and the development of an antibody response could provide similar or even better protection than do the currently used SARS-CoV-2 vaccines, although antibody responses induced by SARS-CoV-2 infection are often lower in titers than those induced by vaccination. In this sense, several other studies demonstrated that infection does protect against reinfection, probably in an antibody-dependent manner [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 90%
“…Thus, infection and the development of an antibody response could provide similar or even better protection than do the currently used SARS-CoV-2 vaccines, although antibody responses induced by SARS-CoV-2 infection are often lower in titers than those induced by vaccination. In this sense, several other studies demonstrated that infection does protect against reinfection, probably in an antibody-dependent manner [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 90%
“…A further indicator for the protective effect of a natural SARS‐CoV‐2 infection is the low observed rate of reinfections. 17 , 21 , 22 Individuals who underwent SARS‐CoV‐2 infection are thus generally considered immune for at least a few months. It could therefore, be hypothesized that a single bout of a SARS‐CoV‐2 vaccine might be sufficient for consolidating this protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio observacional retrospectivo, realizado en la población de Austria, se selecciona a las personas que padecieron COVID-19 en la primera oleada y lo sobrevivieron (febrero a abril de 2020) y se compara el riesgo de padecer COVID-19 durante el periodo que va desde el 1 de septiembre al 30 de noviembre de 2020. Se registraron 40 reinfecciones en 14.840 supervivientes del COVID-19 de la primera oleada (0,27%) y 253.581 infecciones en 8.885.640 individuos del resto de la población general (2,85%) [3]. Esto es concordante con el hecho de que la mayoría de pacientes que han pasado la infección mantienen al menos 6 meses la presencia de anticuerpos anti-SARS-CoV-2 IgG y neutralizantes.…”
Section: ¿Cuanto Tiempo Tras Padecer Covid Es Recomendable Esperar Para Vacunarse?unclassified